The effects of stress–tension on depression and anxiety symptoms: evidence from a novel twin modelling analysis. Issue 15 (8th September 2016) - Davey, C. G.; López-Solà, C.; Bui, M.; Hopper, J. L.; Pantelis, C.; Fontenelle, L. F.; Harrison, B. J.
Abstract : Background: Negative mood states are composed of symptoms of depression and anxiety, and by a third factor related to stress, tension and irritability. We sought to clarify the nature of the relationships between the factors by studying twin pairs. Method: A total of 503 monozygotic twin pairs completed the Depression Anxiety Stress Scales (DASS), an instrument that assesses symptoms of depression, anxiety and stress–tension. We applied a recently developed twin regression methodology – Inference about Causation from Examination of FAmiliaL CONfounding (ICE FALCON) – to test for evidence consistent with the existence of 'causal' influences between the DASS factors. Results: There was evidence consistent with the stress–tension factor having a causal influence on both the depression ( p < 0.0001) and anxiety factors ( p = 0.001), and for the depression factor having a causal influence on the anxiety factor ( p < 0.001). Conclusions: Our findings suggest a critical role for stress–tension in the structure of negative mood states, and that interventions that target it may be particularly effective in reducing depression and anxiety symptoms.